Cutaneous Myopericytoma: A Report of 3 Cases and Review of the Literature - Phyu P. Aung; Lynne J. Goldberg; Meera Mahalingam; Jag Bhawan (MDPI AG, 2015)
Cutaneous myopericytoma is a rarely reported mesenchymal neoplasm with a benign biologic behavior. It is seen more commonly in males and typically occurs in adults on the distal extremities. To the best of our knowledge, there are only 13 reports describing 45 cases of cutaneous myopericytoma in the literature. The 3 cases in this report expand the clinical presentation and reinforce the histopathologic features of cutaneous myopericytoma. While the clinical presentation in 2 cases (located on the scalp and heel) was in keeping with that reported previously of a slow-growing painless firm nodule, the third case, located on the dorsal wrist, presented as a scaly keratotic nodule. Histopathologic examination of all 3 cases revealed an unencapsulated dermal nodule with concentric perivascular arrangement of plump, spindle-shaped myoid cells admixed with thin-walled blood vessels. Immunohistochemical staining revealed the lesional cells to be actin- (3/3) and caldesmon- (2/3) positive and negative for other smooth muscle markers, compatible with perivascular myopericytic differentiation.